Gold And Bismuth Nanoparticles Modified Electrodes For Simultaneous Detection Of Pb(II) Ions, Cd(II) Ions And Cu(II) Ions - Tengeo, Chee Ying (Universiti Sains Malaysia, 2022)
Recently, heavy metal pollution in the environmental water has put human health and ecosystem at risk. Several spectroscopic techniques have been used for heavy metal detection. However, these techniques are costly, require experienced operators and are inappropriate for on-site analysis. Electrochemical sensors can overcome these constraints but they have low sensitivity towards heavy metal detection. Therefore, by modifying working electrode with nanoparticles, the sensitivity of the electrode can be improved. In this work, gold nanoparticles (AuNPs) were fabricated on indium-tin oxide (ITO) working electrode by electrodeposition method. The electrochemical properties of modified electrode were studied by cyclic voltammetry (CV) and square wave anodic stripping voltammetry (SWASV) was performed for heavy metal detection. AuNPs/ITO electrode prepared in 0.1 M HNO3 with unheat-treated and uncleaned conditions was selected as the optimum as the electrode exhibited better electrochemical performance and high sensitivity towards heavy metal detection. The linear range of Pb(II), Cd(II) and Cu(II) was 10 ppb to 50 ppb with sensitivities of 0.121 μA ppb-1 cm-2, 0.109 μA ppb-1 cm-2 and 0.039 μA ppb-1 cm-2 and limits of detection (LOD) of 26.16 ppb, 21.17 ppb and 50.68 ppb, respectively. A promising sensing platform was demonstrated by electrode co-modified with bismuth nanoparticles (BiNPs) and AuNPs. Comparing with AuNPs/ITO electrode, the synergistic effect of Bi-AuNPs on ITO electrode showed improved electrochemical performance and better stripping response in heavy metal detection.